Analysis of the Influence of Consumption Value on Green Purchase Intention of Environmentally Friendly Fuel Mediated by Green Trust - Reza Ichsan Rizaldi; Achmad Fachrodji (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine and analyze the influence of functional value, conditional value, environmental value and green trust as mediating variables on green purchasing intention of RON 95 products. The population used in this study were respondents who had used environmentally friendly fuels. The method used in this study was non-probability sampling with a sampling technique using the Purposive sampling technique, while the sample criteria were users of environmentally friendly fuels and refueled in the DKI Jakarta area with a sample size of 100 respondents. The data analysis method applied in this study was the Structural Equation Model-Partial Least Square (SEM-PLS). Where the results of this study show that functional value, conditional value, environmental value have positive and significant results on green trust and green purchasing intention. While green trust also has positive and significant results directly on green purchasing intention, as well as mediating positively and significantly the three consumption values ​​(functional value, conditional value, & environmental value) on green purchasing intention.